Isolation of cellulolytic bacteria from oil palm mesocarp waste: ISOLATION OF CELLULOLYTIC BACTERIA FROM OIL PALM MESOCARP WASTE - K PARANI; P VEERA LAKSHMI (Journal of Oilseeds Research, 2026)
In the present study, eight bacterial isolates were obtained from oil palm mesocarp waste-dumped soil using the serial dilution and pour plate methods. The isolates were characterized based on microscopic examination and biochemical tests, including starch hydrolysis, gelatin hydrolysis, casein hydrolysis, catalase activity, methyl red test, Voges-Proskauer test, and glucose fermentation. Among the eight bacterial isolates, four exhibited prominent phosphate- and potash-solubilizing abilities as well as nitrogen-fixing activity on their respective agar media. Two isolates, OPMW 5 and OPMW 7, showed maximum degradation of carboxymethyl cellulose (CMC), with the highest ratio of clear-zone diameter (25 mm) to colony diameter (10 mm) on Congo red agar plates, resulting in a cellulolytic index of 2.5. These values were higher than those recorded for the other isolates, namely OPMW 1, OPMW 2, OPMW 3, OPMW 4, and OPMW 6. Furthermore, the highest cellulase activity (0.19 IU/mL) was recorded for isolate OPMW 5 when grown in CMC broth, indicating its superior ability to degrade cellulose through the production of cellulolytic enzymes.